Nate the Great and the pillowcase - Sharmat, Marjorie Weinman; Weinman, Rosalind; Simont, Marc (New York : Yearling, 2006)
Nate the Great investigates the disappearance of a homemade pillowcase belonging to Rosamond's cat Big Hex.
Includes 32 pages of extra fun activities.
490L
Decoding demand: 65 (high) Semantic demand: 78 (high) Syntactic demand: 59 (medium) Structure demand: 80 (high)
Keywords: Pillowcases -- Fiction; Nate the Great (Fictitious character) -- Fiction; Child detectives -- Fiction; Mystery and detective stories; Fiction